The Role of Risk Perception in Social Media Influence, Overconfidence, and Investment Decisions - Trii Nurhayati; Eliada Herwiyanti (Universitas Pancasakti Tegal, 2026)
This study examines the effects of Social Media Influence and Overconfidence on Investment Decision, with Risk Perception serving as a mediating variable among retail stock investors in Indonesia. A quantitative approach was employed using survey data collected from 86 retail stock investors through purposive sampling. Data were analyzed using multiple regression analysis and Hayes' PROCESS Macro Model 4. The results indicate that Overconfidence and Risk Perception have positive and significant effects on Investment Decision. In addition, Social Media Influence and Overconfidence positively influence Risk Perception. However, Social Media Influence was found to have a significant negative direct effect on Investment Decision. The mediation analysis further revealed that Risk Perception significantly and partially mediates the relationships between Social Media Influence and Investment Decision, as well as between Overconfidence and Investment Decision. These findings suggest that investment decisions are influenced not only by external information obtained through social media but also by investors’ perceptions of risk. This study contributes to the behavioral finance literature by highlighting the important role of Risk Perception in explaining investment decision-making behavior among retail investors.